Value of Viral Nucleic Acid in Sputum and Feces and Specific IgM/IgG in Serum for the Diagnosis of Coronavirus Disease 2019 - He, Yuwen; Luo, Jiangyan; Yang, Jie; Song, Jinlong; Wei, Li; Ma, Weifeng (Frontiers in Cellular and Infection Microbiology, 2020)
new type of coronavirus-induced pneumonia eventually termed “coronavirus disease 2019” (COVID-19) was diagnosed in patients in Wuhan (Hubei Province, China) in December 2019, and soon spread worldwide. To improve the detection rate of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), we analyzed the results of viral nucleic acid and serum-specific antibody tests on clinical samples from 20 patients with SARS-CoV-2 infection diagnosed at the First Affiliated Hospital of Guangzhou Medical University in China. By comparing various sample types collected from COVID-19 patients, we revealed multiple pathways for SARS-CoV-2 shedding, and a prolonged detectable period for viral nucleic acid test in sputum specimens, demonstrating that the timeline of the viral shedding is of great value in determining the time of release from quarantine or discharge from hospital. We also recommend for the application of serological test to assist in confirming SARS-CoV-2 infection judged by viral nucleic acid test, especially when COVID-19-related symptoms have appeared and the viral nucleic acid test was negative. Our findings are critical for the diagnosis of SARS-CoV-2 infection and for determining deadline of restriction measures to prevent transmission caused by convalescent patients with COVID-19.